2017
DOI: 10.1177/1098612x17740247
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of zonisamide on interictal electroencephalography in familial spontaneous epileptic cats

Abstract: Objectives The effectiveness of zonisamide (ZNS) against spontaneous epilepsy in cats has not yet been described. The purpose of this study was to investigate the effect of ZNS on interictal paroxysmal discharges (PDs) using scalp electroencephalography (EEG) in familial spontaneous epileptic cats (FSECs). Methods Eight FSECs were evaluated (six males and two females). Scalp EEG measurements were performed once a week for 3 weeks before ZNS administration (Pre-ZNS). Thereafter, administration of ZNS was starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Existing studies on zonisamide in cats are limited. [8][9][10] While zonisamide appears safe and well-tolerated in cats clinically, the efficacy of zonisamide for seizure control and the prevalence of adverse effects have not been established in cats with seizures. 3,11 The primary goal of this study was to retrospectively identify epileptic cats receiving zonisamide as part of their seizure management and to evaluate monthly seizure frequency before and after starting zonisamide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies on zonisamide in cats are limited. [8][9][10] While zonisamide appears safe and well-tolerated in cats clinically, the efficacy of zonisamide for seizure control and the prevalence of adverse effects have not been established in cats with seizures. 3,11 The primary goal of this study was to retrospectively identify epileptic cats receiving zonisamide as part of their seizure management and to evaluate monthly seizure frequency before and after starting zonisamide.…”
Section: Discussionmentioning
confidence: 99%
“…Zonisamide is effective in animal models for controlling focal and generalized seizures, and clinical studies in dogs receiving zonisamide have shown 60% efficacy as a monotherapy and 60‐80% efficacy as an add‐on therapy. Existing studies on zonisamide in cats are limited 8‐10 . While zonisamide appears safe and well‐tolerated in cats clinically, the efficacy of zonisamide for seizure control and the prevalence of adverse effects have not been established in cats with seizures 3,11 …”
Section: Introductionmentioning
confidence: 99%
“…The TLE group included 17 FSECs (Nos. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and one cat with TLE not related to FSEC strain (No. 18).…”
Section: Animalsmentioning
confidence: 99%
“…As one factor of this, EEG in cats with highdensity coats and hard scalps requires strict sedation and immobilization for electrode placement and stable recording. Some studies have reported the use of sedatives, typically medetomidine (MED) or the enantiomer of MED, dexmedetomidine, to perform scalp EEG in dogs and cats (8)(9)(10). MED and dexmedetomidine produce sedative and analgesic effects enough for EEG recording and can be rapidly antagonized by the administration of atipamezole (11,12).…”
mentioning
confidence: 99%
“…Antiepileptic drugs (AED) administered in cats, include phenobarbital (PB), levetiracetam (LEV), and zonisamide (ZSD) (Bailey and Dewey, 2009;Ukai et al, 2018).The effectiveness of treatment is evaluated by a more than 50% reduction in seizures, thus marking a successful dosage regimen. On the contrary, a reduction of less than 50% or an increase in the number of seizures is indicative of progressive disease, refractory seizures, poor client compliance or inadequate dosing (Bailey and Dewey, 2009).…”
Section: Introductionmentioning
confidence: 99%